Effects on physiochemical parameters of water samples by non-thermal plasma treatment (Journal of Nepal Physical Society, 2024)
Non-thermal plasma (NTP) is a rapidly advancing multidisciplinary field, gaining recognition for its environmentally friendly and chemical-free attributes. Over the past decade, NTP has drawn considerable interest due to its extensive potential applications, particularly in the realm of water treatment. When applied to water, NTP creates an acidic environment, which significantly modifies several key properties, including pH, electrical conductivity, and turbidity. Additionally, the process generates reactive oxygen and nitrogen species (RONS), which induce notable changes in the chemical composition of the water. These unique characteristics of plasma-treated water present a promising alternative for microbial disinfection. In our research, NTP is generated at atmospheric pressure using a high-voltage power supply operating at 12 kV and 50 Hz. The plasma discharge produced under these conditions is thoroughly examined through electrical and optical diagnostic methods to ensure accurate characterization. Various water samples, including those collected from river, tap, and well, are treated using a non-thermal plasma source. After treatment, the physicochemical parameters of the water samples are systematically analyzed to assess the impact of plasma treatment and to highlight its potential applications in water purification and disinfection.